Relations between patient personality and patients' dissatisfaction after multifocal intraocular lens implantation: clinical study based on the five factor inventory personality evaluation - Rudalevicius, Paulius; Auffarth, Gerd U. (Eye, 2020)
To assess the level of visual function and the influence of personality traits on patients’ (pts) satisfaction with the visual function following the four different MIOL implantation. We evaluated the visual outcomes over a 6 months follow-up period after cataract surgery with bilateral implantation of four different multifocal IOLs. The spectacle independence, photic phenomena, the influence of personality traits on patients’ satisfaction with the visual function were assessed. A total of 170 eyes of 85 pts were included. There was no statistically significant difference in UDVA (F = 1.6 p = 0.177) and CNVA (F = 1.2 p = 0.30) between the groups 6 months after the surgery. The ReSTOR group had a worse CDVA than the M-flex (p = 0.019) and TECNIS (p = 0.005) groups. The ReSTOR and AT.LISAtri groups had a statistically significantly better UNVA than the M-flex (p = 0.020 and p = 0.013) and TECNIS groups (p = 0.001 both). The independence on spectacles for near distance was from 71.8% (in M-flex group) to 100% (in ReSTOR). The answers of the pts with the prevailing neurotic personality type contradicted the answers given by the pts with other prevailing personality types (p < 0.01). MIOL implantation helped ensure better postoperative visual acuity, but some pts were unhappy with the postoperative outcomes. It was established that the subjective satisfaction or dissatisfaction of patients after MIOL implantation is related to certain personality traits: pts with neuroticism as the dominant personality trait were least happy with the postoperative outcomes; pts with conscientiousness and agreeableness as dominant personality traits demonstrated the highest satisfaction with the postoperative outcomes.
Published online: 20 September 2019
Gesehen am 03.07.2020